2020
DOI: 10.1108/jarhe-02-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Affective events theory as a theoretical lens for improving the working environment of academics in developing economies

Abstract: PurposeThe rapid pace of progress in academic institutions in developing economies has created stressful and relatively toxic workplaces, resulting in different negative organizational outcomes indicating the need to transform universities into healthier academic workplaces. However, a review of the higher education literature in both developed and developing countries shows that the antecedents and consequences of academics' affective states has been a relatively unexplored area. Hence, our study aims at test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
(60 reference statements)
2
24
0
Order By: Relevance
“…Our findings are generally in alignment with previous research works guided by AET. For instance, with regard to the work environment feature and attitude linkages, our findings were consistent with the findings of Wegge et al (2006), Ghasemy et al (2019), andGhasemy, Erfanian, andGaskin (2020). With respect to the relationships between work environment features and work events, our findings were in line with the results of studies such as Matthews et al (2010); Lam and Chen (2012); Ghasemy, Morshidi, et al (2021); and Ashkanasy et al (2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are generally in alignment with previous research works guided by AET. For instance, with regard to the work environment feature and attitude linkages, our findings were consistent with the findings of Wegge et al (2006), Ghasemy et al (2019), andGhasemy, Erfanian, andGaskin (2020). With respect to the relationships between work environment features and work events, our findings were in line with the results of studies such as Matthews et al (2010); Lam and Chen (2012); Ghasemy, Morshidi, et al (2021); and Ashkanasy et al (2014).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Ghasemy et al (2019), in a study in the HE context, provided evidence for the impacts of involvement, workload, and welfare, as work environment features, on role conflict, as a negative work event. Moreover, the findings in the study by Ghasemy, Erfanian, and Gaskin (2020) revealed that three work environment features, namely, supervisory support, involvement, and welfare are significant predictors of both role conflict and interpersonal conflict in academic institutions.…”
Section: The Indirect Effect Of Work Environment Features On Attitudesmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, Rezvani et al (2016), in the context of Australian defense industry, found empirical evidence for the positive relationship between emotional intelligence of project managers and their job satisfaction, trust and project success. Finally, in the context of HE, Ghasemy, Erfanian, and Gaskin (2020) and Ghasemy, Mohajer, et al (2020) found empirical evidence for the contribution of affective states to faculty’s job satisfaction. In line with these research findings, we developed the following two hypotheses:…”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…While the review of the literature shows that the issues related to the internationalization and globalization in HE have gained the attention of the researchers (see Bourn, 2011; Hamann & Zimmer, 2017; Larbi & Fu, 2017; Lau & Lin, 2017; McAllum, 2017), the area of the daily affective experiences of the faculty has remained as a relatively unexplored area within the literature. More specifically, only limited studies (e.g., Ghasemy, Erfanian, & Gaskin, 2020; Ghasemy et al, 2019; Ouweneel et al, 2012) were found in HE context focusing on the antecedents and consequences of academics’ emotions.…”
Section: Introduction and Contextmentioning
confidence: 99%